UNDERSTANDING MORE MATHEMATICS PEDAGOGICAL CONTENT KNOWLEDGE - Ramadian Radite; Eka Sulistyawati (Universitas Cokroaminoto Palopo, 2023)
The effectiveness of mathematics learning activities in the classroom is influenced by many factors such as the psychology of student learning, the level of material being taught, the classroom atmosphere, and the knowledge of the mathematics teacher. A mathematics teacher must at least have in-depth knowledge of mathematics content, strong pedagogical knowledge, and sophisticated technology knowledge. The integration of mathematics content knowledge and pedagogic knowledge makes mathematics pedagogical content knowledge (MPCK) unique as teachers must understand science, philosophy, and dimensions of mathematics, and then integrate it into learning activities so that learning objectives are achieved. A systematic review approach was carried out in this study by reviewing 29 out of 221 articles based on the results of analysis from searches with various keywords. The results showed that MPCK has specifications in terms of definition, aspects, linkages with various aspects of learning, methods of assessment and evaluation, improving method, teacher characteristics, and the impact on a mathematics lesson. This research supports mathematics teachers' efforts to implement effective mathematics learning by understanding more MPCK and optimizing MPCK.